A Comparative Analysis of Pesantren and Formal School Curricula Based on Prevailing Government Regulations - Hiidayat, Cecep; Annasir, Harun (JSP: Jurnal Studi Pesantren, 2025)
The curriculum serves as the cornerstone of the educational process, functioning as a guideline for learning implementation across all educational institutions. In the Indonesian context, pesantren (Islamic boarding schools) and formal schools possess distinct characteristics, yet both are officially recognized within the national education system. This study addresses the growing need to understand the similarities and differences between pesantren and formal school curricula as regulated by government policies, and explores how integration and synchronization can be achieved within the national education framework. This study analyzes the comparison between pesantren and formal school curricula based on existing government regulations, including Law No. 20 of 2003 on the National Education System, Government Regulation No. 55 of 2007 on Religious and Religious Education, and other curriculum implementation policies. A descriptive qualitative method with a document study approach was employed. The findings reveal that while similarities exist in basic curriculum structures such as competency achievement and learning assessment, significant differences emerge in educational goals, content, and pedagogical approaches. Pesantren emphasize religious dimensions and character development rooted in Islamic values, whereas formal schools orient more toward national competency standards. The study concludes that dialogue and curriculum integration are essential to building an equitable, adaptive, and socially responsive education system in Indonesia.